Implementation of Auteur Theory in The Butler (2013): Race-Relationship between Whites and Blacks - Triastama Wiraatmaja (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2018)
The objectives of this study are to show the depiction of racism, which are followed by prejudice and discrimination towards black Americans based on context-relationship with The Butler (2013) during 1920s until 1960s. This article used a qualitative method with auteur theory, mise-en-scene and thick description. Based on The Butler (2013), this study show that racism, which were followed by prejudice and discrimination towards blacks, emerged caused by slavestereotyping which stressed blacks as inferior and whites that uphold white-supremacy concept, as superior. Apparently that through The Butler, Lee Daniels wants to highlight that actually public policies or government laws which regulate citizens’ civil rights and slavery are not adequate to restrain or eradicate racism towards blacks American.